Functionalization of 3D Polylactic Acid Sponge Using Atmospheric Pressure Cold Plasma - G. Gatti; D. D’Angelo; M. Errahali; M. Biasizzo; L. Marchese; F. Renò (International Journal of Polymer Science)
The deposition of organic functionalities on biomaterials to immobilize biomolecules is a research area of great interest in the medical field. The surface functionalization of a 3D porous scaffolds of PDLLA with carboxyl (-COOH) and amino (-NH2) groups by cold plasma treatment at atmospheric pressure is described in this paper. Two methods of continuous and pulsed plasma deposition were compared to assess the degree of functionalization of the internal porous 3D scaffold. In particular, the pulsed plasma treatment was found to functionalize uniformly not only the sample surface but also inside the open cavities thanks to its permeability and diffusion in the porous 3D scaffold. The species developed in the plasma were studied by optical emission spectroscopy (OES) technique, while the functionalization of the sponges was evaluated by the Diffuse Reflectance Fourier-Transform Infrared Spectroscopy (DR-FTIR) technique using also the adsorption of ammonia (NH3) and deuterated water (D2O) probe molecules. The functional groups were deposited only on the front of the sponge, then the structural characterization of both front and back of the sponge has demonstrated the uniform functionalization of the entire scaffold.